Development of LKPD Assisted by Augmented Reality (AR) Media on Chemical Bonding Materials to Improve Student Learning Outcomes - Ryni, Alivia Putri; Sukarmin, Sukarmin (FKIP - Universitas Riau, 2025)
Chemical bonds are a concept that is often considered abstract by students because of the limitations of direct experience to understand the occurrence of chemical bonds. This research developed a Student Worksheet (LKPD) assisted by Augmented Reality (AR) media that allows students to see and understand the shape of chemical bonds in 3D animation. The development process of this LKPD follows the modified Research and Development (R&D) method of Borg and Gall, consisting of three stages: preliminary study, development, and testing. The results of the validation test get a ≥4 mode which means that it is practical from the validation sheet. The results of the practicality test obtained percentages of 80% and 90%, meaning practical and very practical, based on student response questionnaires and student observation sheets. The results of the effectiveness test showed that a significant value of 0.000 was less than 0.05 indicating a significant average difference in student learning outcomes. Research shows that the use of LKPD assisted by AR media can improve students' learning outcomes on chemical bonding materials.